Do robots pose a threat to public revenues? - Pavel Semerád; Milena Otavová; Lucie Semerádová; Andrea Hrdličková; Bettina Matzka (Trendy v podnikání, 2020)
The paper is focused on the area of introducing new technologies and the consequent impact on a more efficient functioning of a company, with an emphasis on reducing labour costs. A case study has been created for a company that replaced its employees with technology to reduce the dependence of its performance on the staff. Our aim was to quantify the impact of this managerial decision on the company, as well as to quantify the negative impact on the state budget. With this decision, the company will not only reduce its dependence on its staff, but also its labour costs by 88.14% while the performance will remain the same. It can be assumed that this will also have a significant impact on the sustainability of public finances, as the state will suffer a loss of income in the case of personal income tax as well as social/health insurance; the mandatory expenditure may also increase, such as in the case of paying social benefits to the unemployed. In view of the sustainability of public finances, the paper proposes recommendations that could address this negative impact.